A multicenter comparison of PD-L1 protein and mRNA expression in urothelial bladder cancer by immunohistochemistry and RT-qPCR (Checkpoint-Typer(C)): A round robin test by the BRIDGE-Consortium Germany - Eckstein, Markus; Wirtz, R.; Pfannstil, C.; Wach, S.; Stoehr, R.; Breyer, J.; Erlmeier, F.; Guenes, C.; Nitschke, K.; Weichert, W.; Otto, W.; Keck, Bastian; et al. (2018)
EVALuna2:34065

Low cytoplasmic and nuclear KPNA2 expression in radiotherapy-treated head and neck squamous cell cancer is associated with an adverse outcome - Erben, Pia; Brunner, Kathrin; Hecht, Markus; Haderlein, Marlen; Buettner-Herold, Maike; Agaimy, Abbas; Fietkau, Rainer; Hartmann, Arndt; Distel, Luitpold (International Journal of Clinical and Experimental Pathology, 2015)
KPNA2 has effects on carcinogenesis, cell differentiation and transcriptional regulation. KPNA2 has been linked to DNA damage repair by its role to import the DNA double strand break repair complex MRN into the nucleus. The aim of our study was to evaluate the prognostic value of KPNA2 expression in both cytoplasmic and nuclear location in patients with HNSCC treated with radio(chemo)therapy.225 patients with HNSCC treated with neoadjuvant, definitive or adjuvant radio(chemo)therapy were included. Immunohistochemical staining was performed on tissue micro arrays to evaluate nuclear and cytoplasmic KPNA2 expression.The median fraction of tumor cells with nuclear KPNA2 expression was 15%. 47% of tumor samples showed positive cytoplasmic staining. Patients with low nuclear as well as negative cytoplasmic expression tended to have an unfavorable prognosis. There was no correlation between nuclear and cytoplasmic KPNA2 expression. Low nuclear combined with negative cytoplasmic KPNA2 had a clearly unfavorable prognostic effect in local failure-free survival (P=0.014), metastasis-free survival (P=0.001) and no evidence of disease (P=0.008). A combination of low nuclear/negative cytoplasmic with high nuclear/high cytoplasmic KPNA2 expression was prognostically unfavorable with regard to tumor specific survival (P=0.021) and to a lower extent to overall survival (P=0.18). In multivariate analysis low nuclear/negative cytoplasmic versus any high KPNA2 (P=0.008) and T-category (P=0.002) proved as independent prognostic variables.The combination of nuclear and cytoplasmic KPNA2 expression is a potential excellent prognostic parameter in HNSCC treated with radio(chemo)therapy.
EVALuna2:6796